Exploring Linkable Ring Signatures to Ensure Anonymity and Authenticity in Survey Research: A Methodological Design Proposal and Architectural Model - Chagas, Francisco das; Tomaz, Emerson B.; Araújo, Allysson Allex (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Survey research holds significant importance in various areas related to Information Systems (IS), spanning from academia to the business context and public governance. However, it is common for many research endeavors to face challenges related to the data authenticity, whether due to unauthorized access by individuals or incorrect responses stemming from a lack of anonymity for participants. This paper presents an ongoing research endeavor aimed at developing a web application based on Linkable Ring Signatures scheme capable of enabling the anonymous authentication of participants in surveys. In particular, this objective of this paper lies in the methodological design proposal and an architectural model. Regarding the contributions for IS research and practice, we introduce a novel architectural model based on the Linkable Ring Signature to ensure anonymous authenticity in survey research. We also emphasize the importance of fostering trust in survey participation and its design/process.